2014
DOI: 10.1093/hmg/ddu089
|View full text |Cite
|
Sign up to set email alerts
|

CRB2 acts as a modifying factor of CRB1-related retinal dystrophies in mice

Abstract: Mutations in the CRB1 gene lead to retinal dystrophies ranging from Leber congenital amaurosis (LCA) to early-onset retinitis pigmentosa (RP), due to developmental defects or loss of adhesion between photoreceptors and Müller glia cells, respectively. Whereas over 150 mutations have been found, no clear genotype-phenotype correlation has been established. Mouse Crb1 knockout retinas show a mild phenotype limited to the inferior quadrant, whereas Crb2 knockout retinas display a severe degeneration throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 43 publications
2
80
0
4
Order By: Relevance
“…The high interindividual variability in disease onset, retinal thickness on OCT, and VF sizes supports the earlier suggestion of the involvement of genetic and possibly environmental modifiers in CRB1-associated disease. 47 In mice, Crb2 is a modifier of Crb1, 48 and human CRB2 can rescue the phenotype in mice lacking Crb1. 15 Sequence variants in human CRB2 cause a renal and cerebral syndrome with possible loss of BCVA and EZ loss on OCT in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…The high interindividual variability in disease onset, retinal thickness on OCT, and VF sizes supports the earlier suggestion of the involvement of genetic and possibly environmental modifiers in CRB1-associated disease. 47 In mice, Crb2 is a modifier of Crb1, 48 and human CRB2 can rescue the phenotype in mice lacking Crb1. 15 Sequence variants in human CRB2 cause a renal and cerebral syndrome with possible loss of BCVA and EZ loss on OCT in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout Crb1 -/-, knockin Crb1 C249W/-, and naturally occurring Crb1 rd8/rd8 mice show mild retinal disorganization that is particularly marked in the inferior retinal quadrant [van de Pavert et al, 2007;Pellissier et al, 2014]. Mouse models of Crb1 loss of function together with models of Crb2 and Pals1 loss of function also display some of the phenotypic features associated with human CRB1 variants, including focal laminar disorgani zation, pseudorosette formation, photoreceptor degeneration, and functional impairment in the electroretinogram [Alves et al, 2013[Alves et al, , 2014Kim et al, 2015].…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…This apical localization is essential for maintaining the polarity of the epithelia and adhesion among retinal and lens cells. Therefore, retinas with deficient Pals1 or Crb1, Crb2 and Crb1/Crb2 display laminar disorganization, retinal folding and pseudorosette formation (Alves et al, 2014a; Alves et al, 2013; Cho et al, 2012; Park et al, 2011; Pellissier et al, 2014; Zou et al, 2013). The specificity of the antibodies used in the present study was previously demonstrated.…”
Section: Resultsmentioning
confidence: 99%